Revision of Nearctic species of Lonchodryinus Kieffer 1905, with description of a new species from New Mexico (Hymenoptera: Dryinidae) - Olmi, Massimo; Guglielmino, Adalgisa (Zootaxa, 2010)
Lonchodryinus politus new species, is described from New Mexico, Eddy County (USA). A revision of the three Nearctic species of Lonchodryinus Kieffer 1905 is presented. New data on geographic distribution of L. bakeri (Kieffer 1906) and L. flavus Olmi 1984 are given. A key to the Nearctic species of Lonchodryinus is presented.